Analysis of Blockchain Integration in Carbon Trade Management: A Perspective on Forest Cover and REDD+ Schemes in Indonesia - Haryono, Haryono; Rahman, Arief; Zainal, Rifki Fahrial; Santoso, Bagus Teguh; Endarto, Budi (Westscience Press, 2025)
The integration of blockchain technology in carbon trade management offers transformative potential for improving transparency, monitoring, and efficiency in Indonesia's REDD+ schemes. This study employs a qualitative approach, analyzing data from three informants—a blockchain expert, an environmental policymaker, and a conservationist—using NVivo software for thematic analysis. Findings reveal that blockchain enhances transparency and trust, streamlines Monitoring, Reporting, and Verification (MRV) processes, and addresses challenges in carbon trade systems. However, barriers such as infrastructure gaps, high implementation costs, and regulatory ambiguities remain. The study underscores the need for targeted capacity building, pilot programs, and robust policy frameworks to enable effective blockchain adoption in Indonesia's carbon markets.